Population Genetic Structure and Colonisation History of the Tool-Using New Caledonian Crow - Abdelkrim, Jawad (Public Library of Science, 2012)
New Caledonian crows exhibit considerable variation in tool making between populations. Here, we present the first study of the species’ genetic structure over its geographical distribution. We collected feathers from crows on mainland Grande Terre, the inshore island of Toupéti, and the nearby island of Maré where it is believed birds were introduced after European colonisation. We used nine microsatellite markers to establish the genotypes of 136 crows from these islands and classical population genetic tools as well as Approximate Bayesian Computations to explore the distribution of genetic diversity. We found that New Caledonian crows most likely separate into three main distinct clusters: Grande Terre, Toupéti and Maré. Furthermore, Toupéti and Maré crows represent a subset of the genetic diversity observed on Grande Terre, confirming their mainland origin. The genetic data are compatible with a colonisation of Maré taking place after European colonisation around 1900. Importantly, we observed (1) moderate, but significant, genetic differentiation across Grande Terre, and (2) that the degree of differentiation between populations on the mainland increases with geographic distance. These data indicate that despite individual crows’ potential ability to disperse over large distances, most gene flow occurs over short distances. The temporal and spatial patterns described provide a basis for further hypothesis testing and investigation of the geographical variation observed in the tool skills of these crows.